A STUDY ON CORRELATION BETWEEN SELF-EFFICACY AND ACADEMIC ACHIEVEMENT IN INDONESIAN CONTEXT - Murtiningsih, Sri Rejeki (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
There have been a number of research studies that point out that students’ self-efficacy has a close relationship with their academic achievement. Giving speeches in English requires a high level of self-efficacy because confidence and English skills are both needed when performing the assignment in front of an audience and examiners. This research tries to investigate the students’ self-efficacy in giving speeches in EFL classes and their performance, which is reflected in their academic achievements. The research involved 89 non-English department university students in a non- English speaking country. The speech course was given to the students in their fourth semester after they completed English courses focusing on reading and writing, speaking and listening, and extensive reading in their first, second and third semester respectively. Questionnaires are distributed to the students to find out their level of self-efficacy. Their achievements were assessed based on the rubrics provided and distributed to the students at the beginning of the course. The data were then analyzed using SPSS.The research found that self-efficacy in English speech delivery did correlate to the academic achievement.